Connection Between Internet Using Habits and Ethical Attitude of Business Students - Barizsné Hadházi, Edit; Kiss, Zsuzsanna (International Journal of Engineering and Management Sciences, 2017)
In these days we are witnessing a trend of more and more using IT assets and the using of internet too. As teachers at the university we can see that our students also tied with a thousand threads to the IT world. Current research aims to explore the students’ internet using habits, how many times they spend on the web  and why. In our previous work we examined our economist students’ ethical attitudes. In this study we try to connect this two themes. Our research question: are there any connection between our students’ ethical judgment and their internet using habits.